Focus on Outcomes: Fostering Systemic Departmental Improvements - Christopher Geanious; Daniel L Reinholz; Joel Christopher Corbo; Karen Falkenberg; Mary E Pilgrim; Sarah B. Wise (To Improve the Academy, 2021)
This article describes how a focus on outcomes can be a tool for guiding systemic change. By focusing on positive outcomes to be achieved, a group can guide its collective efforts toward an ideal future rather than becoming fixated on individual problems to solve. While there is support for an outcome-guided approach in the literature on individual and organizational change, this approach has not been used extensively to support department-level changes in science, technology, engineering, and mathematics (STEM) education.